2022
DOI: 10.52711/0974-360x.2022.00685
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1, BCL2, and the RB Tumor Suppressor have abnormal expressions in lung cancer

Abstract: The retinoblastoma (RB) gene encodes the retinoblastoma pocket protein, which controls the cell cycle by binding to unphosphorylated E2F transcription factors and inhibiting their activation. The function of BRCA1 and the anti-apoptotic protein Bcl-2 in lung cancer, however, is still debated. Objective:The purpose of this research is to look at the relationship between the cell-cycle proteins BRCA1, BCL2, and RB and lung cancer etiology and progression. Experimental Design: Cases from major hospitals and many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In this context, a study by Jassim et al, (2022) on malignant lung tumors found abnormal expressions of some other tumor suppressor proteins such as BRCA1, BCL2, and the RB. Likewise, (Jassim et al, 2021) on tumor suppressor protein "p53" in breast cancerous tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a study by Jassim et al, (2022) on malignant lung tumors found abnormal expressions of some other tumor suppressor proteins such as BRCA1, BCL2, and the RB. Likewise, (Jassim et al, 2021) on tumor suppressor protein "p53" in breast cancerous tumors.…”
Section: Discussionmentioning
confidence: 99%